2020
DOI: 10.1021/acsanm.9b02505
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of Metallic-Nanodimer Thermoplasmonics for Phototactic Nanoswimmers

Abstract: We assess the potentiality of several geometries of metallic nanodimers (one of the simplest thermoplasmonic systems) as candidates for active particles (nanoswimmers) propelled and controlled by light (phototaxis). The studied nanodimers are formed by two spherical nanoparticles of gold, silver, or copper with radii ranging from 20 to 100 nm. Contrary to most proposals, which assume the asymmetry of the systems as a requirement for self-propulsion, our results show that nanodimers made of identical nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Their velocity can reach 8.9 µm s −1 (Figure 8C). Furthermore, Bertoni et al [60] suggested that simple symmetric structures of metal nanodimers (Au, Ag, and Cu) have strong phototropism by theoretical calculations. Among them, symmetric Ag homodimers with radii between 20-40 nm were the best candidates.…”
Section: Design Of Mnms With Phototaxismentioning
confidence: 99%
“…Their velocity can reach 8.9 µm s −1 (Figure 8C). Furthermore, Bertoni et al [60] suggested that simple symmetric structures of metal nanodimers (Au, Ag, and Cu) have strong phototropism by theoretical calculations. Among them, symmetric Ag homodimers with radii between 20-40 nm were the best candidates.…”
Section: Design Of Mnms With Phototaxismentioning
confidence: 99%
“…Trajectory loops were created using a diverging laser beam. An interesting Janus-like configuration was also proposed [ 33 ], having pairs of spherical particles, where each pair consisted of two particles of different materials and providing estimates for the thermophoretic forces and velocities. This brings us to the idea of designing special micro-motors based on the JP concept (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This persistence length increases the diffusion constant of the Brownian particle. The aforementioned property has been verified experimentally, , and various propulsion mechanisms to induce a net nonreciprocal force have been proposed, such as chemical reactions, external illumination, ultrasound, and magnetic and electric fields. , Speckle patterns have been used to promote out of equilibrium dynamics, , and the use of optical forces, applied currently to promote binding, , have been proposed in the literature to induce active motion . However, an analysis of an active propulsion driven by nonreciprocal optical forces in a isotropic radiation environment is still lacking.…”
mentioning
confidence: 98%